Role of the Tide on the Structure of the Amazon Plume: A Numerical Modeling Approach. Issue 2 (15th February 2020) - Ruault, Valentin; Jouanno, Julien; Durand, Fabien; Chanut, Jérôme; Benshila, Rachid
Abstract: The dynamical balance on the Amazon shelf and its implication on the properties of the Amazon River plume is not fully understood and poorly represented in global‐ and basin‐scale ocean models. In this study, the sensitivity of the Amazon shelf dynamics to tidal forcing is explored with a set of high‐resolution numerical simulations (1/36°) with and without the tide. A comparison of the simulations with sea surface salinity in situ measurements at 5°N (a location where the plume seasonally detaches from the coast and retroflects toward the east) revealed that the explicit resolution of the tide significantly improves the representation of the offshore spread of the river plume. This study further highlights the finding that tidal currents affect the properties of the whole Amazon plume. This sensitivity is explained by a near total collapse of the northwestward alongshore mean flow located near the river mouth, once the tidal forcing is included. This weakening of the ambient flow reduces (i) the dilution ratio between the ambient salty shelf waters and the riverine freshwaters and (ii) the constraint on the cross‐shore extension of the low‐salinity bulge. With tides, the plume is fresher near the river mouth (by up to 5 units), more extended in the cross‐shore direction, and more easily exported offshore by the North Brazil Current at the shelf break. Key Points: The sensitivity of the Amazon shelf dynamics to tidal forcing is explored with a set of high‐resolution numerical simulations Explicit resolution of the tides significantly improves the representation of the offshore spread of the river plume With tides, the plume is more easily exported offshore by the North Brazil Current at the shelf break